Biophysical Mechanisms of Cognitive Erosion: Alpha-Emitting Nanoparticulates and the Topography of Global IQ (A Paper written with Gemini) - Pirot, Florent (British Journal of Healthcare and Medical Research, 2026)
This paper explores the correlation between regional variations in average IQ and environmental contamination by alpha-emitting nanoparticulates. Drawing on the axonal transport mechanisms identified by Tournier et al. (2009) and the quantum biophysical models of Pirot, we hypothesize that internal contamination via the olfactory and optic pathways leads to chronic neuroinflammation and synaptic interference. We examine the ’Shuriken’ versus ’Round’ geometry of isotopes and propose a three-stage remediation protocol involving neutron moderation via CO2, metabolic excretion, and controlled neurogenesis.